The Impact of Forward-Looking Metrics on Employee Decision-Making: The Case of Customer Lifetime Value - Casas-Arce, Pablo; Martínez-Jerez, F. Asis; Narayanan, V. G. (The Accounting Review, 2017)
ABSTRACT This paper analyzes the effects of forward-looking metrics on employee decision-making. We use data from a bank that started providing branch managers with the customer lifetime value (CLV)—an estimate of the future value of the customer relationship—of mortgage applicants. The data allow us to gauge the effects of enriching the employees' information set in an environment where explicit incentives and decision rights remained unchanged. On average, customer value increased 5 percent after the metric's introduction. The metric's availability resulted in a significant shift in attention toward more profitable client segments and some improvement in cross-selling. However, the use of CLV did not negatively impact pricing or default risk, as the literature predicts. Finally, branch managers with shorter tenure displayed a stronger response, consistent with information substituting for experience.